Apatites Record Sedimentary Provenance Change 4–5 Myrs Before Clay in the Oligocene/Miocene Alpine Molasse - Hülscher, Julian; Sobel, Edward R.; Kallnik, Niklas; Hoffmann, J. Elis; Millar, Ian L.; Hartmann, Kai; Bernhardt, Anne (Frontiers in Earth Science, 2022)
Extracting information about past tectonic or climatic environmental changes from sedimentary records is a key objective of provenance research. Interpreting the imprint of such changes remains challenging as signals might be altered in the sediment-routing system. We investigate the sedimentary provenance of the Oligocene/Miocene Upper Austrian Northern Alpine Foreland Basin and its response to the tectonically driven exhumation of the Tauern Window metamorphic dome (28 ± 1 Ma) in the Eastern European Alps by using the unprecedented combination of Nd isotopic composition of bulk-rock clay-sized samples and partly previously published multi-proxy (Nd isotopic composition, trace-element geochemistry, U-Pb dating) sand-sized apatite single-grain analysis. The basin offers an excellent opportunity to investigate environmental signal propagation into the sedimentary record because comprehensive stratigraphic and seismic datasets can be combined with present research results. The bulk-rock clay-sized fraction εNd values of well-cutting samples from one well on the northern basin slope remained stable at ∼−9.7 from 27 to 19 Ma but increased after 19 Ma to ∼−9.1. In contrast, apatite single-grain distributions, which were extracted from 22 drill-core samples, changed significantly around 23.3 Ma from apatites dominantly from low-grade (<upper amphibolite-facies) metamorphic sources with Permo-Mesozoic and late Variscan U-Pb ages and εNd values of −4.4 to dominantly high-grade metamorphic apatites with late Variscan U-Pb ages and εNd values of −2.2. The change in apatite single-grain distributions at 23.3 Ma is interpreted to result from the exposure of a new Upper Austroalpine source nappe with less negative εNd values triggered by the ongoing Tauern Window exhumation. Combining these data with the clay-sized bulk-rock εNd values reveals that the provenance changed 4–5 Myrs later at 19 Ma in the clay-sized fraction. Reasons for the delayed provenance-change recording are rooted in the characteristics of the applied methods. Whereas single-grain distributions of orogen-wide sediment-routing systems can be dominated by geographically small areas with high erosion and mineral fertility rates, bulk-rock methods integrate over the entire drainage basin, thus diminishing extreme values. Hence, by combining these two methods, spatial information are uncovered, enabling a previously unattained understanding of the underlying environmental change.